2014
DOI: 10.1080/03004430.2014.940931
|View full text |Cite
|
Sign up to set email alerts
|

Making oneself heard – children's experiences of empowerment in Swedish preschools

Abstract: Children's experiences of empowerment in relation to preschool peers and in childadult interactions were studied, involving 25 four-to six-year-olds from four Swedish preschools. Group interviews using puppets comprised pre-constructed scenarios to examine preschools' activities. Children took photos of indoor and outdoor preschool environments, followed by a photo-elicitation interview. Data were analysed by content analysis. Results showed that authority was expressed in relation to teachers and parents. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
(48 reference statements)
0
15
0
4
Order By: Relevance
“…Furthermore, PEI used with children acknowledges them as active participants in their own lives (Almqvist & Almqvist, 2015;Clark, 1999). Young children can be disadvantaged in traditional interviews because they may have neither the cognitive and social skills to participate in questionand-answer dialogue, the language skills to understand particular questions, nor the ability to explain their understanding of certain concepts or experiences (Crivello, Campfield, & Woodhead, 2009).…”
Section: Purposesmentioning
confidence: 99%
“…Furthermore, PEI used with children acknowledges them as active participants in their own lives (Almqvist & Almqvist, 2015;Clark, 1999). Young children can be disadvantaged in traditional interviews because they may have neither the cognitive and social skills to participate in questionand-answer dialogue, the language skills to understand particular questions, nor the ability to explain their understanding of certain concepts or experiences (Crivello, Campfield, & Woodhead, 2009).…”
Section: Purposesmentioning
confidence: 99%
“…Notably, these studies implemented various hands-on activities which were not found to be common in the literature reviewed. Some of these activities implied children creating a mind-map (McEvilly, 2015), children completing a story told by an adult (White, 2016), the use of vignettes and scenarios to elicit children's views (Almqvist and Almqvist, 2015), children leading a housetour (Merewether, 2015) (Fleer and Li, 2016), and projective techniques by using the Pictorial Measure of School Stress and Wellbeing (pmssw) interview (Harrison and Murray, 2005). Now, we will give a closer look at the evidence pertaining to the strategies identified.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to what we found with the interviews, group discussions varied in terms of the organisation and material used by researchers to prompt children's narratives. We found that some researchers conducted group discussions while children were drawing and writing (Harwood and Copfer, 2015;Leigh, 2015;Wahle et al, 2017), while others used puppets (Almqvist and Almqvist, 2015;Katz and McLeigh, 2017). Other studies triggered discussions by using a range of attractive activities for children, such as "blob trees" or "message in a bottle" (Adderley et al, 2015) and with the use of photos taken by children (Koch, 2018;Merewether, 2015).…”
Section: Universidad Pedagógica Nacional Colombiamentioning
confidence: 98%
“…En säker och statusfylld position i kamratgruppen, och att man därmed kan räkna med kamraternas stöd, visar sig ge bättre möjligheter att påverka och göra sig hörd. Är man dessutom språkligt aktiv och använder ett språk som harmonierar med pedagogernas förstärks graden av inflytande (Almqvist & Almqvist, 2015;Elvstrand, 2009;Lanå ,2015). Det motsatta, att inta en tyst position, ger enligt Öhrn (2005) betydligt mindre utrymme för att påverka skeendet i klassrummet.…”
Section: Pedagogernas Betydelse För Inflytandeunclassified